KAJIAN IMPLEMENTASI UNDANG-UNDANG NOMOR 28 TAHUN 2009 DI KOTA SURABAYA - Sholikhah, Muslikhatus (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
Based on the research result shows that the Implementation of Regulation No. 28 in 2009 in regards to the local tax and local retribution to the Local Own Source Revenue (PAD) in the city of Surabaya is effective. It can be seen that in the budgeting year from 2009 to 2012 has been increasing but has not reached the target. In the budgeting year of 2013 is already effective in order to reach the target which is Rp 2.191.375.125.979 or 103.45%. The growth of local tax has increased in the average in absolute term by Rp 1.229.998.704.282 or 49%each year. The local retribution shows from budgeting year from 2009 to 2012 has been fluctuating and has not reached the target yet. In the budgeting year of 2013 is already effective in reaching the expected target ofRp 235.826.209.899 or 100.27%. The Growth of local retribution has increased in the average in absolute term by Rp 194.616.312.622 or 8.55%each years. Keywords: Effectiveness, Local Tax, Local Retribution, Local Own Source Revenue (PAD).